From cooperative practice to research and back: learning from the emotional experience of ethnography with two social enterprises - Langmead, Kiri (Emerald, 2017)
Purpose: The paper explores how experiences and emotions arising from the performance of ethnography shape the construction of knowledge about democratic practice in two social enterprises. It argues that ethnographer’s can develop a more nuanced understanding of organisational practices by moving beyond the self-reflexive work of being aware of ones position to embrace the emotional work of engaging reflexively with this position.